Influence of dates of sowing on growth attributes, phenology and yield performances of diverse wheat varieties under changing climate in Eastern sub-Himalayan plains - Tripathy, Bidusi; Singha Roy, Ashish Kumar; Mitra, Biplab (Journal of Cereal Research, 2025)
Influence of dates of sowing on growth attributes, phenology and yield performances of diverse wheat varieties under changing climate in Eastern sub-Himalayan plains Bidusi Tripathy, Ashish Kumar Singha Roy and Biplab Mitra Department of Agronomy, Uttar Banga Krishi Viswavidyalaya, Pundibari, West Bengal-736 165 Â Abstract An experiment was carried out during 2017-18 and 2018-19 at sub-Himalayan plains of West Bengal to find out the optimum time of sowing for higher growth and yield performances of diverse wheat varieties (Triticum aestivum L.) and to quantify the yield losses due to delayed sowing. The experiment was laid out in split plot design having 24 treatment combinations in 3 replicates. Four different dates of sowing (November 5, November 25, December 15 and January 05) were randomly allotted in each main plot, while six wheat varieties (HS 562, HD 2967, HD 3086, HI 1544, MACS 6222 and WR 544) were randomly allocated in sub-plots. The height of plants, tiller number as well as LAI recorded at different stages of growth during both the years differed significantly with different dates of sowing. All these growth attributes were recorded higher under November 25 sowing. The total biomass production (101.1 and 90.7 q ha-1 during 2017-18 and 2018-19, respectively) was significantly higher on the same date of sowing over the other dates. The number of spikes m-2, number of filled grains spike-1 as well as 1000-grain weight were also influenced significantly by various dates of sowing. The maximum number of spikes m-2 (273 and 274 during 2017-18 and 2018-19, respectively), filled grains spike-1 (41 and 39 in 2017-18 and 2018-19, respectively) as well as 1000-grain weight (40.56 and 39.72 g during 2017-18 and 2018-19, respectively) were obtained under November 25 sowing. The crop sown on November 25achieved maximum yield (41.48 and 40.6 q ha-1 during 2017-18 and 2018-19, respectively) over the other dates of sowing during both the years of experiment. The variety HD 2967 (31.7 and 37.1 q ha-1 during 2017-18 and 2018-19, respectively) achieved maximum grain yield followed by variety MACS 6222 (28. 9 q ha-1) during 2017-18 and HD 3086 (34.6 q ha-1) during 2018-19. December 15 sowing recorded an estimated overall yield reduction of 40.7 kg ha-1 day-1 over November 25 sowing and at the same time November 05 sowing also resulted in a yield decrement of 42.7 kg ha-1 day-1 indicating the optimum sowing window in late November for eastern sub-Himalayan plains. Keywords: Wheat, growth attributes, yields, time of sowing, variety DOI.10.25174/2582-2675/2020/98540